Recent progress and current challenges of immunotherapy in advanced/metastatic esophagogastric adenocarcinoma. (November 2022) - Moehler, Markus; Högner, Anica; Wagner, Anna D.; Obermannova, Radka; Alsina, Maria; Thuss-Patience, Peter; van Laarhoven, Hanneke; Smyth, Elizabeth
Abstract: The new era of immunotherapy is successfully implemented in the treatment of metastatic/locally advanced esophagogastric adenocarcinoma (EGAC), as it has been investigated in combinations with/without chemotherapy in human epidermal growth factor receptor 2 (Her2)-positive and Her2-negative tumors. Recent approvals of immune checkpoint inhibitors (ICI) enrich the therapeutic landscape in nearly every therapeutic line. Based on CHECKMATE-649, the combination of nivolumab and chemotherapy in first-line therapy of programmed cell death protein 1 (PD-L1)-positive patients with advanced gastroesophageal junction cancer (GEJC), esophageal cancer (EC), and gastric cancer (GC) was approved in Europe for PD-L1 combined positivity score (CPS) ≥ 5 patients and independently from PD-L1 score in the USA and Asia. Based on KEYNOTE-590, patients with advanced GEJC and EC qualify for the combination of pembrolizumab plus chemotherapy in Europe (CPS ≥ 10) and the USA. For Her2-positive patients, trastuzumab with first-line chemotherapy plus pembrolizumab has beneficial response rates and resulted in approval in the USA (KEYNOTE-811). In third-line therapy, superior overall survival (OS) was achieved by the administration of nivolumab (approval in Japan, ATTRACTION-02), and pembrolizumab shows a positive effect on the duration of response (KEYNOTE-059). Questions of resistance to immunotherapy or the role of gender in response to ICI need to be clarified. This review provides an overview of the current approvals of ICI in advanced EGAC and reflects results of relevant phase II/III trials with focus on possible biomarkers, including PD-L1 CPS and microsatellite-instability (MSI) status. Highlights: Newly approved immune checkpoint inhibitors (ICI) enrich options for GEJ/GC therapies. Relevant phase II/III trials focus on important biomarkers including PD-L1 assessment. Next research may clarify ICI resistance mechanisms and varied gender responses.